ANALISA JALAN RING ROAD NGAWI STA 3+200 – STA 6+200 KABUPATEN NGAWI PROPINSI JAWA TIMUR - Eko Nurfadzilah; Sigit Winarto; Yosef Cahyo (Kadiri University, 2018)
Transportation has an important role in people's lives. As time goes by, the increase in vehicle volume affects traffic performance which results in congestion, one of which is on the road from Surabaya to Solo and vice versa. So an alternative road was built called the Ring Road Ngawi road construction project with the aim of diverting traffic away from heavy vehicles. This study aims to find the thickness of the pavement construction of the road, to control the geometric of the road, drainage channels and RAB. The method used is data analysis. The result of this road project planning calculation is a road shoulder of 2 m and a total pavement width of 7 m with the road type 2/2 UD. For the pavement thickness planning with a plan age of 10 years, the total thickness is 73 cm. As well as the geometric control of the road on the horizontal alignment using the Full Circle curve at point PI2 and using the Spiral-Circle-Spiral curve at the points PI3 and PI4. For rectangular drainage planning with stone masonry with finishing, the dimensions are b = 1m, d = 0.5m, and w = 0.5m. The RAB required is IDR 10,917,623,500. Transportasi memiliki peran penting bagi kehidupan masyarakat. Seiring berkembangnya waktu peningkatan volume kendaraan mempengaruhi kinerja lalu lintas yang mengakibatkan kemacetan, salah satunya pada ruas jalan dari arah Surabaya menuju Solo dan juga sebaliknya. Maka dibangun jalan alternatif yang disebut proyek pembangunan jalan Ring RoadÂ Ngawi dengan tujuan mengalihkan lalu lintas dari kendaraan berat. Penelitian ini bertujuan untuk mencari tebal perkerasan konstruksi jalan, mengontrol geometrik jalan, saluran drainase dan RAB. Metode yang digunakan adalah analisa data. Hasil dari perhitungan perencanaan proyek jalan ini adalah bahu jalan 2 m dan lebar perkerasan total 7 m dengan tipe jalan 2/2 UD.Â Untuk perencanaan tebal perkerasan jalan dengan umur rencana 10 tahun diperoleh tebal total 73 cm. Serta kontrol geometrik jalan pada alinyemen horizontal menggunakan lengkung Full Circle pada titik PI2 dan menggunakan lengkung Spiral-Circle-Spiral pada titik PI3 dan PI4. Untuk perencanaan drainase berbentuk segi empat dengan bahan pasangan batu kali dengan finishing diperoleh dimensi b = 1m, d = 0,5m, dan w = 0,5m. RAB yang dibutuhkan sebesar Rp 10.917.623.500,-.